Gemini imaging of QSO host galaxies at z ∼ 2 - Croom, S; Schade, D; Boyle, B; Shanks, T; Miller, L; Smith, R (Institute of Physics Publishing, 2004)
We present results of a Gemini adaptive optics (AO) imaging program to investigate the host galaxies of typical QSOs at z ∼ 2. Our aim is to study the host galaxies of typical L*QSO QSOs at the epoch of peak QSO and star formation activity. The large database of faint QSOs provided by the Two-Degree Field QSO Redshift Survey allows us to select a sample of QSOs at z = 1.75-2.5 that have nearby (<12″ separation) bright stars suitable for use as AO guide stars. We have observed a sample of nine QSOs. The images of these sources have AO-corrected FWHM of between 0″.11 and 0″.25. We use multiple observations of point-spread function (PSF) calibration star pairs to quantify any uncertainty in the PSF. We then factored these uncertainties into our modeling of the QSO plus host galaxy. In only one case did we convincingly detect a host (2QZ J133311.4+001949, at z = 1.93). This host galaxy has K = 18.5 ± 0.2 mag with a half-light radius Re = 0″.55 ± 0″.1 equivalent to ∼3L*gal, assuming a simple passively evolving model. From detailed simulations of our host galaxy modeling process, we find that for four of our targets we should be sensitive to host galaxies that are equivalent to ∼2L*gal (passively evolved). Our nondetections therefore place tight constraints on the properties of L*QSO QSO host galaxies, which can be no brighter (after allowing for passive evolution) than the host galaxies of L*QSO active galactic nuclei at low redshift, although the QSOs themselves are a factor of ∼50 brighter. This implies that either the fueling efficiency is much greater at high redshift or that more massive black holes are active at high redshift.